Social Conflict That Portrayed In "The House On Mango Street" Novel - Wildan, Muhammad; Muhajir, Fatimah; Sudirman, Eka Pratiwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
Social conflict can be defined as a battle over values, and claims to limited status, power, and resources in which the opponent's goal is to neutralize, harm, or eliminate their rival. Social conflict also refers to disagreements and tensions that arise between different groups of people in society. This study aimed to explore two categories of social conflict presented in Sandra Cisneros' The House on Mango Street: realistic and nonrealistic conflict. The researcher analyzed the novel using a sociological approach, focusing on social conflict by Lewis Coser as a central theme. Elements such as realistic and nonrealistic conflict are examined in the context of the social struggles faced by the novel's characters. The researcher argues that social conflict has the potential to influence and transform human behavior and attitudes within society. Utilizing qualitative methods, the study investigates the experiences and social realities of the characters. Data were collected from words, phrases, clauses, sentences, and paragraphs related to social conflicts throughout the narrative. The analysis reveals that indirect characterization through dialogue and character behavior is a key feature of the novel, with no direct characterization being evident. The study identifies various social conflicts, particularly between Esperanza, an immigrant, and other characters. The findings indicate that realistic conflicts emerge when Esperanza faces disappointment and sexual harassment from her peers. Additionally, nonrealistic conflicts are portrayed through tension in some situations, such as distrust and jokes from her friends that trigger conflicts.